IN VITRO CYTOTOXIC AND ANTI-HIV ACTIVITY OF PHYLLANTHUS NIRURI WHOLE PLANT EXTRACTS - RAJENDRA PRASAD GUJJETI; ESTARI MAMIDALA (International Journal of Pharma and Bio Sciences, 2015)
HIV is the etiological agent of AIDS that has created major health care problem throughout the world. The aim of the present study is to evaluate the cytotoxic effects and anti-HIV activity of Phyllanthus niruri whole plant extracts. Hexane, chloroform, ethyl acetate, acetone and methanol solvents were used to prepare the extracts by sequential maceration method. RetroSys HIV-1 RT (Innovagen, Sweden) kit was used to determine the anti-HIVactivity of all solvents extracts. Cytoxicity study was performed on all extracts by MTT assay using PBMC’s. All extracts exhibited the most notable activity. The chloroform and hexane extracts of Phyllanthus niruri showing highest (88.7% and 87.8%) HIV-RT inhibition at 2mg/ml concentration. While control drug (AZT) showing 91.7% at 2mg/ml concentration. IC50 value of all extracts determined below 40mg/ml. This result suggests that Phyllanthus niruri whole plant extracts contains medicinally important bioactive compounds towards anti-HIV.